Examining Sex Differences in Visual Reliance During Postural Control in Intercollegiate Athletes - Nicolette Ingel; Victoria Vice; Courtney Dommer; Jennifer Csonka; Tara Moore; Ariel Zaleski; Carolyn Killelea; Mallory Faherty; Jody Feld; Timothy Sell (International Journal of Sports Physical Therapy)
# Background